1988
DOI: 10.1136/jnnp.51.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Motor control deficits of orofacial muscles in cerebral palsy.

Abstract: SUMMARY Voluntary control of the masseter and orbicularis oris superioris muscles was examined in able bodied and cerebral palsied subjects using visual tracking tasks. A smoothed measure of muscle activity (the full-wave rectified and low-pass filtered electromyogram) was presented as a marker on a computer display screen and the subjects could control the vertical position of the marker by voluntarily altering the level of isometric contraction of one of the muscles. A target marker was also displayed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
(11 reference statements)
0
9
0
1
Order By: Relevance
“…The range of voluntary joint rotation increased significantly in two children, only one of whom had a significant reduction in spasticity. This may reflect the dissociation between spasticity and voluntary control which has been reported in a number of studies of cerebral palsy (Milner-Brown and Penn 1979, Neilson and McCaughey 1982, Barlow and Abbs 1984, Brown et al 1987, Vaughan et al 1988. Voluntary control may have improved in these two children, independent of the level of spasticity, as a result of 'practice' at maximum joint rotation.…”
Section: Discussionmentioning
confidence: 82%
“…The range of voluntary joint rotation increased significantly in two children, only one of whom had a significant reduction in spasticity. This may reflect the dissociation between spasticity and voluntary control which has been reported in a number of studies of cerebral palsy (Milner-Brown and Penn 1979, Neilson and McCaughey 1982, Barlow and Abbs 1984, Brown et al 1987, Vaughan et al 1988. Voluntary control may have improved in these two children, independent of the level of spasticity, as a result of 'practice' at maximum joint rotation.…”
Section: Discussionmentioning
confidence: 82%
“…Facial muscles do not act on joints, they have few or no proprioceptors, and their motoneurons neither undergo reciprocal inhibition nor possess the axon collaterals needed to receive recurrent inhibition. [34][35][36][37] Hence, BT injected into facial muscles is unlikely to alter sensory input, and other mechanisms must be evoked to explain BT-induced central effects. Remarkably, altered facial motor output commonly leads to cortical reorganization.…”
Section: Into the Facial Districtmentioning
confidence: 98%
“…Ries and Berzin (2005) compared children with CP and healthy children, using the modified Ashworth scale for measuring the degree of spasticity in places where a higher incidence of changes in jaw movements was observed, such as lateral deviations and protrusions, in children with CP. Other studies show no correlation between the severity of TMD and the degree of spasticity (VAUGHAN, NEILSON and O'DWYER, 1988;MARIA, 2002). Alfaro, Gonzalez, Robles et al (1999) demonstrated that the masseteric inhibitor reflex obtained in young individuals and adults with CP is not altered by the disease's subgroup (spastic group or athetosis group), but by the patients' type of occlusion.…”
Section: Resultsmentioning
confidence: 99%
“…According to Maria (2002) and Vaughan, Neilson and O'Dwyer (1988), patients with CP who are more neurologically compromised have higher functional involvement of the masticatory system and structural involvement of the temporomandibular joint (TMJ). This is undoubtedly due to the increase in muscle spasticity, and limitations in jaw movements.…”
Section: Introductionmentioning
confidence: 99%